The Impact of the 5E Learning Cycle Model on Students’ Motivation in Islamic Education - Erlando Dimas Dwi Putra; Jamal Fakhri; Beti Susilawati (MAN 4 Kota Pekanbaru, 2026)
This research investigates the effectiveness of the 5E Learning Cycle instructional model in improving students’ learning outcomes and academic engagement motivation in Islamic Religious Education at SMP Negeri 11 Bandar Lampung. The research was conducted in response to preliminary findings indicating low levels of student motivation, particularly in intrinsic learning drive, which reached only 18%. A quasi-experimental posttest-only control group design was employed, involving two randomly selected Grade VII classes: an experimental group taught using the Learning Cycle 5E model and a control group receiving conventional instruction. The research instrument was a structured learning motivation questionnaire initially consisting of 15 items. Following the validity analysis, 10 items met the required criteria and were retained for further analysis. The reliability test conducted on these valid items yielded a Cronbach’s Alpha coefficient of 0.704, indicating an acceptable level of internal consistency. Accordingly, this reliability coefficient is consistently reported throughout the manuscript to ensure methodological clarity and avoid interpretative bias. Data were analyzed using tests of normality, homogeneity, and an independent sample t-test. The results revealed a statistically significant difference between the experimental and control groups (p < 0.05), indicating that the Learning Cycle 5E model effectively improved students’ learning motivation. Notable improvements were observed in enthusiasm, responsibility, independence, and active engagement. This research provides empirical evidence supporting the effectiveness of the 5E instructional model in enhancing the quality of the learning process and improving students’ academic engagement Islamic Religious Education beyond science-based instruction.